The immediate challenges for the European Central Bank - Dornbusch, Rudiger 1942-2002; Favero, Carlo A. 1962-; Giavazzi, Francesco 1949- (1998)
This paper discusses a number of issues that the newly constituted Board of the ECB will face early on. We show how conducting a European monetary policy is very different from living under the protective umbrella of the Bundesbank. We discuss voting on the ECB Board and argue that the ability to communicate to the public will be a critical factor for the success of the new institution. We also ask how a single monetary policy -- a common change in the interest rate controlled by the ECB -- is transmitted to the economy of the member countries. We show that the monetary process differs significantly inside EMU: initially disinflation episode could thus fall very unequally on a few member countries because they have a combination of financial structure that spreads a monetary contraction widely structure that is relatively inflexible. This process, moreover, is sure to evolve of the financial industry restructuring that is already underway and will be accentuated by the common money. Furthermore, as the Lucas principle suggests, the wage-price process itself will adapt to the changing focus of European monetary policy.
Keywords: Banque centrale européenne; European Central Bank; Politique monétaire - Europe; Monetary policy -- Europe; Europa